SENI LUKIS DAN SENI GORES PADA MEGALITIK PASEMAH PROVINSI SUMATERA SELATAN - Kristantina Indriastusti (Jurnal Penelitian Arkeologi Papua dan Papua Barat, 2011)
The art of painting has emerged thousands of years ago in prehistoric society as an expression of their religious to the ancestor spirits and the power of natural forces around, as well as the lives ofprehistoric humans settled in the highlands pasemah, as an expression of their lives better either by nature or strength of their ancestors expressed in the form of paintings that depicted in various forms and styles. The presence of prehistoric paintings in Pasemah have a specific meaning in life relegi affiliated-but very valuable their magical beauty.